2003
DOI: 10.1248/bpb.26.911
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study on the Multi-constituents of Huangqin-Tang Decoction in Rats

Abstract: Using a validated high-performance liquid chromatographic (HPLC) method, the pharmacokinetics of multi-constituents in Huangqin-Tang decoction were simultaneously studied both in the compound prescription and in each single herb decoction. At different intervals (0, 1, 2, 4, 8, 12, 24, 36, 48 h) after oral administration of the Huangqin-Tang decoction or a single herb decoction at a dose of 10 g x kg(-1), the concentrations of the constituents and their metabolites: baicalin (BG), wogonoside (WG), oroxylin-A-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 10 publications
1
54
0
Order By: Relevance
“…Schisandra lignans are the major constituents of Schisandra chinensis and more than 40 of them have been isolated, in which the most abundant ingredients include schisandrin, lignans, deoxyschizandrin etc. Several papers focused on how the individual component in the compound prescription interact with other ingredients (Zuo et al, 2003;Bochu et al, 2005;Di et al, 2006;Lu et al, 2007). Schisandra lignans have been shown to have various biological activities, they are usually considered as the main pharmacological effective compounds (Hancke et al, 1999), such as hepatoprotective effect, potent antioxidative property, anticarcinogenic activity through the activation of key liver enzymes and strong inhibitory effect on human immunodeficiency virus reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…Schisandra lignans are the major constituents of Schisandra chinensis and more than 40 of them have been isolated, in which the most abundant ingredients include schisandrin, lignans, deoxyschizandrin etc. Several papers focused on how the individual component in the compound prescription interact with other ingredients (Zuo et al, 2003;Bochu et al, 2005;Di et al, 2006;Lu et al, 2007). Schisandra lignans have been shown to have various biological activities, they are usually considered as the main pharmacological effective compounds (Hancke et al, 1999), such as hepatoprotective effect, potent antioxidative property, anticarcinogenic activity through the activation of key liver enzymes and strong inhibitory effect on human immunodeficiency virus reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were focused on single licorice compounds such as glycyrrhizic acid (Makino et al, 2008), liquiritigenin (Shimamura et al, 1993), and isoliquiritigenin (Guo et al, 2008a,b;Cuendet et al, 2010). Some other studies attempted to detect the in vivo metabolites after licorice extracts were administered (Homma et al, 1997;Zuo et al, 2003;Hou et al, 2005). However, only a few compounds were detected in most reports.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lethality of wogonin by oral administration to mice was low; its LD 50 was 3.9 g/kg (22). Following oral or intravenous administration of wogonin to rats its plasma levels can be measured by a modified HPLC (11,41,47). Tsai et al (41) studied plasma levels of wogonin following its intravenous administration and found that a rapid increase in its plasma level was followed by a prolonged elimination phase.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%